Volume 3: Design, Materials and Manufacturing, Parts A, B, and C 2012
DOI: 10.1115/imece2012-86396
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Quasi-Static Mechanical Properties of a Carbon Fiber Reinforced Carbon Nanotube/Epoxy

Abstract: Carbon fiber reinforced plastics (CFRPs) possess superior in-plane mechanical properties and are widely used in structural applications. Altering the interphase of CFRPs could alleviate the shortcomings of their out-of-plane performance. In this work, the effects of adding multi-walled carbon nanotubes (MWCNTs) to the epoxy matrix of a CFRP are investigated. Two sets of CFRPs with matrices comprising MWCNTs/epoxy and neat epoxy, respectively, were fabricated. The tensile properties of the two systems, namely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Epoxy resins (thermoset polymers) are of significant importance to the engineering field with fibre-reinforced epoxies being applied widely in the aeronautics, automotive, marine and renewable energy industries [1][2][3][4][5][6][7]. Epoxies are characterised by high stiffness, excellent chemical and corrosion resistance, high thermal and mechanical properties, exceptional adhesion to numerous substrates, low shrinkage during cure, outstanding electrical insulating properties, and the good processing ability under various conditions [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins (thermoset polymers) are of significant importance to the engineering field with fibre-reinforced epoxies being applied widely in the aeronautics, automotive, marine and renewable energy industries [1][2][3][4][5][6][7]. Epoxies are characterised by high stiffness, excellent chemical and corrosion resistance, high thermal and mechanical properties, exceptional adhesion to numerous substrates, low shrinkage during cure, outstanding electrical insulating properties, and the good processing ability under various conditions [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have reported that CNTs may be combined with polymers to produce functional composite materials with superior properties. [18,19] Because of the high aspect ratio and the low density, nanometer scale elements as single-walled carbon nanotubes (SWCNTs) and multiwalled carbon nanotubes (MWCNTs) may be used as reinforcing elements in polymer matrices. Also MWCNTs are highly flexible which may improve the interaction and cross-linking with polymer molecules that further enhance morphological feature and ionic conductivity of composite electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Among different inorganic fillers, carbon nanotubes (CNTs), owing to have properties like extremely high strength, high stiffness, and high aspect ratio, are looked upon as ideal nanofillers in the preparation of gel polymer electrolyte. The researchers have reported that CNTs may be combined with polymers to produce functional composite materials with superior properties . Because of the high aspect ratio and the low density, nanometer scale elements as single‐walled carbon nanotubes (SWCNTs) and multiwalled carbon nanotubes (MWCNTs) may be used as reinforcing elements in polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Various Non-Destructive Evaluation techniques (NDE) have been documented to detect damage in composite laminates. Radiographic [201], ultrasonic [202], and lamb wave [203,204] methods have been effectively used to localize damage with high resolution and accuracy. Electromagnetic properties of composites pose an additional challenge in NDE for the assessment with eddy current based methods [205].…”
Section: Introductionmentioning
confidence: 99%